On liability for stalking in the context of the Istanbul convention implementation - Dudorov O.; Dudorova K. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of writing the article is to highlight the issue of criminalization of persecution in the context of the implementation of the Istanbul Convention and to identify ways to improve the Criminal Code of Ukraine. The methodology includes a comprehensive analysis and elaboration of the provisions of the current criminal law of Ukraine and other countries, international legal documents, scientific sources, as well as the formulation of author conclusions and recommendations. The following methods of scientific knowledge were used in the course of the research: logical-semantic, formal-logical, systemic-structural, comparative-legal, modeling. Results. Based on the results of the research: 1) it was established that among the international legal treaties, the Istanbul Convention contains the most comprehensive definition of the concept of persecution as a distinct type of socially unacceptable behavior. It has been proven that, without making certain reservations when ratifying the Istanbul Convention, Ukraine undertook to criminalize persecution. It has also been established that the correspondence between provisions of the current criminal legislation of Ukraine and the corresponding convention provision is fragmentary, and the elimination of the existing legal gap is possible only through legislative amendments; 2) it has been demonstrated that Ukraine’s fulfillment of the corresponding international legal obligation, conditioned by the ratification of the Istanbul Convention, must be balanced, which appeals to relevant foreign experience. When criminalizing stalking in Ukraine, it is advisable to consider the way stalking is described in the Criminal Code of the Federal Republic of Germany, where such type of socially unacceptable behavior is defined clearly and completely. In particular, the establishment of an open list of actions that can be considered as harassment deserves acceptance, because such approach is motivated by a positive desire to cover the variety of behavioral patterns typical for modern stalking and to prevent the possible laxity of the criminal law, for example, due to the development of digital technologies; 3) the fallacy of the approach is argued, according to which the objective aspect of prosecution as a component of a new criminal offense for Ukraine should be determined through an exhaustive list of specified actions. The authors’ version of the disposition of the criminal law norm addressing persecution is proposed for discussion. It has been proven that the article on persecution can be placed either in Chapter III of the Special Part of the Criminal Code of Ukraine (given that personal freedom as the generic object of the relevant criminal offenses, not limited to the physical freedom of a person, includes the freedom of a person in terms of the possibility of choice behavior, the freedom to manage oneself independently and is consistent with the civilized understanding of personal freedom as personal non-proprietor good of an individual), or in Chapter V of the Special Part of the Criminal Code of Ukraine – along with similar in their scope provisions, which are designed to ensure privacy protection and with the help of which separate manifestations of persecution can be considered today. Scientific novelty. Deficiencies of the existing state of legislative provision of criminal law countermeasures against persecution are identified and ways of eliminating these deficiencies, consistent with the provisions of the Istanbul Convention, are proposed. Practical significance. Results of the research can be used in law-making activities to improve the current Criminal Code of Ukraine, as well as the draft of the new Criminal Code of Ukraine.